Isolated and combined dystonia syndromes – an update on new genes and their phenotypes. (29th January 2015) - Balint, B.; Bhatia, K. P.
<x xml:space="preserve">Abstract</x> Recent consensus on the definition, phenomenology and classification of dystonia centres around phenomenology and guides our diagnostic approach for the heterogeneous group of dystonias. Current terminology classifies conditions where dystonia is the sole motor feature (apart from tremor) as 'isolated dystonia', while 'combined dystonia' refers to dystonias with other accompanying movement disorders. This review highlights recent advances in the genetics of some isolated and combined dystonic syndromes. Some genes, such as ANO3, GNAL and CIZ1, have been discovered for isolated dystonia, but they are probably not a common cause of classic cervical dystonia. Conversely, the phenotype associated with TUBB4A mutations expanded from that of isolated dystonia to a syndrome of hypomyelination with atrophy of the basal ganglia and cerebellum (H‐ABC syndrome). Similarly, ATP1A3 mutations cause a wide phenotypic spectrum ranging from rapid‐onset dystonia‐parkinsonism to alternating hemiplegia of childhood. Other entities entailing dystonia‐parkinsonism include dopamine transporter deficiency syndrome (SLC63 mutations); dopa‐responsive dystonias; young‐onset parkinsonism (PARKIN, PINK1 and DJ‐1 mutations); PRKRA mutations; and X‐linked TAF1 mutations, which rarely can also manifest in women. Clinical and genetic heterogeneity also characterizes myoclonus‐dystonia, which includes not only the classical phenotype associated with epsilon‐sarcoglycan mutations but rarely also presentation of ANO3 gene mutations, TITF1 gene mutations typically underlying benign hereditary chorea, and some dopamine synthesis pathway conditions due to GCH1 and TH mutations. Thus, new genes are being recognized for isolated dystonia, and the phenotype of known genes is broadening and now involves different combined dystonia syndromes.